2018
DOI: 10.1177/0300060518808683
|View full text |Cite
|
Sign up to set email alerts
|

Betatrophin for diagnosis and prognosis of mothers with gestational diabetes mellitus

Abstract: Objectives Betatrophin is a widely used diagnostic marker for type 2 diabetes mellitus (DM), but its clinical utility in diagnosing gestational DM (GDM) is unclear. We evaluated the relationship between betatrophin and the risk of GDM as well as the ability of betatrophin to predict postpartum type 2 DM (PDM). Methods In total, 386 patients were categorized into those with and without PDM. All underwent the oral glucose tolerance test while pregnant. Betatrophin was assessed to examine the diagnostic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…miRNAs have been profiled in previous studies as potential biomarker candidates for diagnosis of onset or progression of GDM as well as adverse outcomes of pregnancy [44]. Most studies [45][46][47][48] compared serum/plasma samples from women with GDM in the early stages of pregnancy (16)(17)(18)(19) week) with samples from non-diabetic control groups. Multiple miRNAs were identified as significantly different in the circulation of women with vs without GDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs have been profiled in previous studies as potential biomarker candidates for diagnosis of onset or progression of GDM as well as adverse outcomes of pregnancy [44]. Most studies [45][46][47][48] compared serum/plasma samples from women with GDM in the early stages of pregnancy (16)(17)(18)(19) week) with samples from non-diabetic control groups. Multiple miRNAs were identified as significantly different in the circulation of women with vs without GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from our group have indicated that postpartum levels of a combination of three lipid species, or IGF1 and IGF binding protein IGFBP2, or C-peptide and ghrelin improve stratification ability [16][17][18] in comparison with traditional risk factors such as age and BMI. Several other metabolites have also been demonstrated to have predictive potential for future type 2 diabetes including betatrophin, 2-, 3-hydroxybutyrate and IL1 receptor antagonist measurements during pregnancy, liver enzymes at 1 year postpartum, and global histone H3 dimethylation in blood cells at 10-20 weeks postpartum [19][20][21][22][23]. Machine learning algorithms have also been used to derive signatures of metabolites or lipid species at 6-9 weeks postpartum, which provide a significantly higher AUC in a receiver operating characteristic (ROC) curve analysis [24,25] compared with standard clinical glucose measurements for prediction of future type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…There are contradicting results from the studies on betatrophin and IR, some studies have suggested that circulating betatrophin levels are elevated in T2DM as well as type 1 diabetes (17-19), while others reported that betatrophin levels were reduced in subjects with diabetes (20). A previous study reported high sensitivity and low specificity of betatrophin for diagnosing GDM, and positive correlation of serum betatrophin with HOMA IR (21). Betatrophin is also known as lipasin for its inhibiting action on lipoprotein lipase and has been shown to increase the serum triglyceride levels (22).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies of our group showed that circulating ANGPTL8 levels decreased in patients with hyperthyroidism (such as Graves's disease) [ 55 ], while increased in patients with subclinical and clinical hypothyroidism [ 8 , 56 ]. Although GDM is accompanied by the increase of circulating ANGPTL8 level [ 57 ], and ANGPTL8 is also considered as a molecular marker for early prediction and prognosis of GDM [ 58 , 59 ], but during normal pregnancy, the circulating ANGPTL8 concentration decreases continuously even if insulin resistance and TG levels increase with the progress of pregnancy [ 60 ]. In general, ANGPTL8 is significantly associated with a variety of metabolically related diseases (or physiological states), which has also been confirmed by some prospective studies as a molecular marker to assist in diagnosis or prognosis.…”
Section: Relationships Between Angptl8 and Metabolic Diseasesmentioning
confidence: 99%